Influence of Pumice Particles on the Mechanical and Morphology Properties of Polyester-Cornhusk Fiber Composites - Nasmi Herlina Sari; Suteja Suteja; I Putu Lokantara; Topan Gusti Wibowo (Journal of Fibers and Polymer Composites, 2022)
The purpose of this study was to look into the performance of a cornhusk fiber (CHF) reinforced polyester composite with pumice powder (PP) as a filler. The influence of varied PP volume fractions on composite tensile, bending, impact, and fracture morphology was studied. Using the hot press process, polyester-CHF composites with varied volume fractions of PP filler, namely 5%, 10%, 15%, 20%, 25%, and 30% wt, were created. The results showed that increasing the PP volume fraction from 5% to 15% enhanced the tensile strength of the polyester-CHF composite. The modulus of elasticity and bending modulus tend to grow when filler Pp decreases from 5% to 30%, but elongation value decreases. Furthermore, the best bending strength and impact toughness of the polyester-CHF composite were produced at a volume fraction of PP filler of 20%. SEM images indicate the presence of CHF pull out in all composite variations as well as the number of voids dependent on the PP filler volume.